Migration, debt, and transnational livelihood: Indian labour diasporas in the GCC states amid the pandemic - Pranav Raj (17933381) (2023)
South Asian labour migration to the GCC States is a debt-financed migration in which labour diasporas mobilise resources from a variety of sources, often at exorbitant interest rates, to cover migration costs. In the event of the COVID pandemic, job losses and involuntary returns compound the problem of debt-financed migration, affecting the transnational livelihood of migrant families. This paper explores how the debt-financed migration shapes the transnational livelihood of Gulf labour diasporas amid the pandemic. Empirically, this paper draws on the experiences of 60 Gulf migrants from the Indian state of Bihar. This study reports that the families diversify their labour resources by joining Gulf labour market and migration generates remittances that provide improved livelihood for their families. Although unforeseen events such as the pandemic may delay migration episodes and thus mount the debt burden on migrants, migrants nevertheless find ways to join the Gulf labour market and erk out a trananational livelihood. Other Information Published in: South Asian Diaspora License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/19438192.2023.2226423